4.8 PLACENTAL NA/K-ATPASE INHIBITOR MARINOBUFAGENIN INDUCES ARTERIAL WALL FIBROSIS IN PREECLAMPSIA - Olga Fedorova; Natalia Aglakova; Yulia Grigorova; Vitalily Reznik; Valintina Zernetkina; Wen Wei; Edward Lakatta; Alexei Bagrov (Artery Research, 2018)
Background: Previous studies implicated cardiotonic steroids, including Na/K-ATPase inhibitor marinobufagenin (MBG), in the pathogenesis of preeclampsia (PE). Immunoneutralization of heightened MBG by Digibind, a digoxin antibody, reduces blood pressure (BP) in patients with PE, and anti-MBG monoclonal antibody lessens BP in a rat model of PE. Recently, we demonstrated that MBG induces fibrosis in cardiovascular tissues via mechanism involving inhibition of Fli1, a nuclear transcription factor and a negative regulator of collagen-1 synthesis. Objectives and Methods: We hypothesized that in PE, elevated placental MBG levels is associated with development of fibrosis of umbilical arteries. Thirty patients with PE (mean BP = 118 ± 4 mmHg; 29 ± 2 years; 35 weeks gest. age) and 26 gestational age-matched normal pregnant subjects (mean BP = 92 ± 2 mmHg; controls) were enrolled in the clinical study. Results: PE was associated with a higher placental MBG level (48.6 ± 7.0 vs. 13.6 ± 2.5 nmol/g; P < .01), four-fold decrease of Fli1 and two-fold increase of collagen-1 in placentae (P < .01) vs. control. PE was associated with five-fold decrease in Fli1 level and two-fold increase in collagen-1 level in the PE umbilical arteries vs. those from the normal subjects (P < .01). Isolated rings of umbilical arteries from the subjects with PE exhibited impaired response to the relaxant effect of sodium nitroprusside, vs. control vessels (EC50 = 141 nmol/L vs. EC50 = 0.9 nmol/L; P < .001). In vitro 10 nmol MBG mimicked effect of PE, and monoclonal anti-MBG antibody reversed this effect. Conclusion: These results demonstrate that elevated placental MBG level is implicated in the development of fibrosis umbilical arteries in PE.